World prehistory - Fagan, Brian M., author.
1 online resource
Keywords: "World Prehistory: The Basics tells the compelling story of human prehistory, from our African origins to the spectacular pre-industrial civilizations and cities of the more recent past. Written in a non-technical style by two archaeologists and experienced writers about the past, the story begins with human origins in Africa some 6 million years ago and the spread of our remote ancestors across the Old World. Then we return to Africa and describe the emergence of Homo sapiens (modern humans) about 350,000 years ago, then, much later, their permanent settlement of Europe, Eurasia, Asia, and the Americas. From hunters and foragers, we turn to the origins of farming and animal domestication in different parts of the world after about 11,000 years ago and show how these new economies changed human existence dramatically. Five chapters tell the stories of the great pre-industrial civilizations that emerged after 5,000 years before present in the Old World and the Americas, their strengths, volatility, and weaknesses. These chapters describe powerful rulers and their ideologies, also the lives of non-elites. The narratives chronicle the rise and fall of civilizations, and the devastating effects of long droughts on many of them. The closing chapter poses a question: Why is world prehistory important in the modern world? What does it tell us about ourselves? Providing a simple, but entertaining and stimulating, account of the prehistoric past from human origins to today from a global perspective, World Prehistory: The Basics is the ideal guide to the story of our early human past and its relevance to the modern world"--